PREVALENCE OF ORAL DISEASES AT ULIN HOSPITAL BANJARMASIN IN 2017-2019 - Apriasari, Maharani Laillyza; Sundah, Serenada Audria; Hamdani, Riky (Odonto : Dental Journal, 2022)
Background: Oral disease is a condition that causes lesions in the oral cavity, which can be influenced by age, gender, and level of education. Oral health is still becoming a problem in society that needs attention. According to basic health research 2018, the prevalence of oral disease in Indonesia remains considerably high reaching 57.6%. Oral diseases have practically been observed in Banjarmasin, yet no research has presented the prevalence of oral diseases in Ulin General Hospital, Banjarmasin. The purpose of this study was to determine the prevalence of oral disease in Ulin Hospital, Banjarmasin in 2017-2019Method: This research is a descriptive study using secondary data from medical record. Sampling method was carried out by total population sampling of oral disease patients who were treated at Oral and Dental Clinic, Ulin Hospital in 2017-2019Result: It showed that out of 102 oral disease patients, there were 78 patients suffering from recurrent aphthous stomatitis (76.5%), 8 patients from oral candidiasis (7.8%), 7 patients from oral squamous cell carcinoma (6.9%), 4 patients from oral submucous fibrosis (3.9%), 3 patients from burning mouth syndrome (2.9%), and 2 patients from allergic stomatitis (2%). Oral diseases were mostly found in over-45-years age group (54.9%), with the highest gender proportion is female reaching of 64.7%. Approximately 31.4% patients had completed high school education. Medical management was given to 60,8% patients with oral diseases.Conclusion: Recurrent aphthous stomatitis was the most common oral disease in Ulin Hospital, in 2017-2019, followed by oral candidiasis and oral squamous cell carcinoma.